Avaliação de desempenho de algoritmos de alocação de comprimento de onda em redes ópticas WDM - BEZERRA, Paulo Henrique Gonçalves (Universidade Federal do Pará, 2012)
In this work we studied Routing and Wavelength Assignment (RWA) algorithms on Wavelength Division Multiplexing Optical Networks. The objective to study the allocation algorithms first-fit, least-used and most-used is based on the strategy used to study the RWA Problem. The strategy builds on the overview of the problem involving the routing algorithms and algorithms for allocating wavelength, and having as a key metric for its blocking probability results. This paper presents a different perspective to the problem and believes that the allocation of wavelengths overlaps in importance to the action of routing in optical networks. This perception occurs when analyzing the problem RWA from the traditional criterion used in establishing a route: choosing the shortest path between origin and destination. Despite the identification of a shortest path is no guarantee in optical networks, it will be used, as is needed for that path, a wavelength appropriate. We used a simulation tool for WDM networks OWNS called to perform an analysis of the RWA problem. The results are presented graphically and in one of the simulations we observed a strong trend towards decrease in blocking probability and a good flow of traffic on the network thereby enabling an increase in transmission capacity of the network. Finally, this paper presents a discussion of the differences and limitations of this work and presents future research directions in this field of study.